Neurenteric cyst of the temporal bone: A case report. (December 2021) - Fan, Timothy; Benaim, Ezer; Lee Diaz, Jorge; MacDonald, Charles
Neurenteric cysts are rare, developmental malformations mainly found in the spinal canal. The authors report on a 29-year-old woman who presented with congenital left-sided hearing loss and a 9 days history of left ear pain and facial weakness (House–Brackmann IV). Radiological examination revealed a complex 7 mm cystic structure involving the petrous and mastoid portions of the left temporal bone. Intraoperatively, a red-brown multicystic mass was discovered and excised completely. Histologic findings showed simple columnar epithelium with goblet cells and bilayers of submucosal musculature, resembling normal intestinal linings. Post resection, the patient regained nearly full facial nerve capabilities (House–Brackmann II) with complete resolution of pain, but no changes to her hearing. The objectives of this case report are to describe the clinical, radiologic, intraoperative, and pathologic characteristics of an extradural temporal neurenteric cyst with sensorineural deficits to contribute to the growing knowledge regarding this rare entity.